2014
DOI: 10.1002/cam4.379
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in bladder cancer pathology and survival: analysis of a population‐based cancer registry

Abstract: Sex differences in bladder cancer pathology and epidemiology have been the focus of recent research. We investigated the epidemiological characteristics and compared bladder cancer pathology and survival between men and women in Japan. A total of 13,184 patients with primary bladder cancer diagnosed from 1954 to 2010 were identified in a large-scale cancer registry database in Kanagawa Prefecture. Using this database, we compared the odds ratios (ORs) for nonurothelial carcinoma (non-UC) using a multiple logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 30 publications
3
37
2
1
Order By: Relevance
“…In the present study, the 5‐year relative survival was 80.3% for men and 67.7% for women. The survival of non‐UC patients was worse than that of UC patients, as previously reported . In either all non‐UC cases or all UC cases, relative survival of women was worse than that of men.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In the present study, the 5‐year relative survival was 80.3% for men and 67.7% for women. The survival of non‐UC patients was worse than that of UC patients, as previously reported . In either all non‐UC cases or all UC cases, relative survival of women was worse than that of men.…”
Section: Discussionsupporting
confidence: 81%
“…Zaitsu et al . reported that the proportion of non‐UC in women was 8.2% and 4.0% in men . Puente et al .…”
Section: Discussionmentioning
confidence: 98%
“…A large, population‐based data set (2004‐2016) of Kanagawa Cancer Registry (KCR), a survey of over nine million people in Kanagawa prefecture that covers approximately 7% of the Japanese population, was used for analysis. Details of the study database have been previously described elsewhere . Briefly, Kanagawa Prefecture, a metropolitan prefecture located next to Tokyo, is the second largest prefecture in Japan, and KCR is one of the largest local cancer registries in Japan.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, clinicopathological variables were included in survival analyses as potential mediating variables, ie, these variables do not confound the association between sex and RCC survival, but rather, they may help to explain the observed differences. Our clinicopathological variables of interest included the following: WHO pathological grade (grades 3 or 4 [high‐grade] vs grades 1 or 2 [low‐grade]), the Union for International Cancer Control TNM stage (stages III and IV [late stage] vs stages I and II [early stage]), and any performed surgeries including radical/partial nephrectomy (yes/no), as well as SES (high SES [with the longest‐held occupational class of managerial or professional workers] vs low SES) and smoking habits (never/ever).…”
Section: Methodsmentioning
confidence: 99%
“…Urothelial carcinoma in ICD-O-3 was defined in accordance with our previous study (Zaitsu et al 2015). Controls were patients with no history of the following tobacco-or alcohol-related diseases: all cancers (C00 to 97 in ICD-10, 140 to 208 in ICD-9), all cardiovascular diseases (I01 to I99 in ICD-10, 390 to 459 in ICD-9), all respiratory diseases (J00 to 99 in ICD-10, 460 to 519 in ICD-9), and all digestive diseases (K00 to K93 in ICD-10, 520 to 579 in ICD-9) (Katanoda et al 2008;Samanic et al 2008).…”
Section: Methodsmentioning
confidence: 99%